Using Music to Increase Math Skill Retention - Yoho, Catherine (Journal of the American Academy of Special Education Professionals, 2011)
Discussions with math teachers, of various grade levels, brought out one consistent observation. Each year, students need to be retaught math concepts that they have been previously taught but have forgotten. With the ever-expanding curriculum of material that teachers need to cover over the course of a school year continually growing, it becomes plausible that not enough time is spent on material for it to be internalized and truly learned, for the long term. The amount of material to be covered will not likely decrease, so what can be done to help the instruction that does take place be more effective? What can be done to help students retain information and be able to recall and use it when needed? My Action Research project evolved to answer the question: "Would using music improve math skill acquisition and retention?"